2013
DOI: 10.1093/tropej/fmt030
|View full text |Cite
|
Sign up to set email alerts
|

Placental weight: Relation to maternal weight and growth parameters of full-term babies at birth and during childhood

Abstract: Human growth is a continuous process. Studies defining placental effect on prenatal and postnatal human growth are few. We studied the anthropometric data of hundred mothers who gave birth at term after an uncomplicated singleton pregnancy, and their infants in relation to their placental weight using linear regression analysis. Mother weight, placental weight, and infant length (BL), weight (BW), and head circumference (HC) were obtained at birth and during childhood period (4.5 ± 2 years) of age. At birth, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
3
12
0
1
Order By: Relevance
“…Using population charts, obese and morbidly obese women had a greater risk of high placental weight (>90 th centile) but after taking account of individual height and weight, in addition to parity, baby gender and gestational age, this relationship was attenuated or no longer significant. This suggests that greater placental weight associated with maternal obesity in this and previous studies 3,4,21,22 is overemphasised, and that placental weight is proportionate to maternal size for more women than hitherto suggested. Further, it is this relative placental weight which is of clinical relevance, particularly when the predicted placental weight for any given size of women is not achieved.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Using population charts, obese and morbidly obese women had a greater risk of high placental weight (>90 th centile) but after taking account of individual height and weight, in addition to parity, baby gender and gestational age, this relationship was attenuated or no longer significant. This suggests that greater placental weight associated with maternal obesity in this and previous studies 3,4,21,22 is overemphasised, and that placental weight is proportionate to maternal size for more women than hitherto suggested. Further, it is this relative placental weight which is of clinical relevance, particularly when the predicted placental weight for any given size of women is not achieved.…”
Section: Discussionmentioning
confidence: 40%
“…The size, morphology, blood flow and nutrient transport functions of the placenta are key determinants of fetal growth velocity and birthweight 1 . Weighing the placenta at delivery is a potentially valuable indicator of its function in utero, and placental weight, birthweight and birthweight:placental weight have been linked to adverse perinatal outcomes and to offspring health in the longer term [1][2][3][4][5][6] . Placental weight has been recorded in the Aberdeen Maternity and Neonatal Databank since the start of data collection in the 1950s and been shown to increase linearly with BMI through underweight to morbidly obese categories 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that placental weight determines the fetal growth and birth weight [12]. In addition, placental growth significantly associates with early childhood growth in full-term infants [13]. Increase in nutrient exchange reflects on the arborisation of the villous and thickness of the chorionic disk [6].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have also shown an association between maternal weight and placenta weight. [20][21][22] Proper maternal nutrition facilitates proper growth and development of the placenta and ultimately the developing fetus. [23] In addition, there was a significant increase in placenta weight with maternal age in the univariable model.…”
Section: Discussionmentioning
confidence: 99%